Exploring Masstige Service Brands: A Study of Brand Happiness and ‎Brand Advocacy Towards Over-The-Top (OTT) Platforms - Arora, Garima; Madaan, Dr. Vandana; Singh, Dr. Sultan (International Journal of Accounting and Economics Studies, 2025)
The present research aims to construct a novel conceptual framework centered on the Stimulus-‎Organism-Response (SOR) theory for describing how customers feel happy and ‎show advocacy for Over-the-Top (OTT) brands. To achieve this, the model was assessed by ‎employing quantitative data analysis. For evaluating the broader applicability of the suggested ‎model, the data gathered from 246 Indian Over-the-Top (OTT) users were analyzed by using ‎Partial Least Squares-Structural Equation Modeling (PLS-SEM). It is found that the predictive ‎power pertaining to the model is moderate, and the data validate all of the proposed associations ‎among the selected variables. Additionally, the current study also provides some insightful ‎theoretical, economic, policy, and managerial implications. The implications for the managers were ‎derived by conducting a priority map analysis to thoroughly examine specific constructs and ‎indicators for understanding the brand advocacy behavior of consumers. This provides insightful ‎information to marketing managers to identify the most important construct and the indicators to ‎focus on‎.